Tool Stocked Analysis On DMU 100 Monoblock DMG Machine Spindle - Riyanto, Agus; Nurul , Panji; Hermawan, Ansor Dadan; Martoni, Imam Faisal (International Journal of Psychosocial Rehabilitation, 2020)
Spindle is a tool from the CNC machine parts that is very important to the manufacture of products. The spindle works by moving the axis that has been programmed before so that it can move according to what was ordered through the program. On the Mori DMU 100 Monoblok DMG engine spindle, there are components including Drawbar, Collets, Gripper and Tools. This component is very instrumental in opening and gripping the tool. The slightest damage to the component results in damage to the product made. The damage that occurs in this machine is that tools are not released automatically from the Spindle according to the program that has been determined. Analysis is carried out to find out why the tool cannot get out of the spindle. Steps taken to determine the cause of damage is to open all components in the Spindle. From the results of the component analysis found on the spindle, there is a loose component, the counter bolt that locks the collet. This is because Collet holds the load and turns the spindle. Repair is done by resetting the counter collet bolt using liquid adhesive so that the position of the collet does not change. Spindle test results after repair shows gripping and removing tools, according to the programmed instructions.